Potential of Functional Food Fortified Alfalfa (Medicago sativa L.) in Fermented Milk Products: A Literature Review - Nasihin, Ahmad; Fadhlurrohman, Irfan (Universitas Brawijaya, 2025)
Alfalfa (Medicago sativa L.) is an herbal plant rich in nutrients such as vitamins, minerals, proteins, and bioactive compounds. Many bioactive compounds contained in alfalfa are flavonoids and phytosterols, making it an ideal ingredient for food fortification. Although it has been widely used in food products, its use in fermented dairy products is still very rare. This literature review aims to explore the potential of alfalfa as a fortifying ingredient for fermented milk products by reviewing various literature related to alfalfa and milk fortification. The literature search method was conducted through various academic databases such as Google Scholar, Scopus, PubMed, and ScienceDirect. The literature search used keywords consisting of “alfalfa”, “milk fortification”, “functional food”, and “fermented dairy products”. The literature review results show that alfalfa can be fortified into fermented dairy products such as yoghurt and kefir. Alfalfa can enhance nutritional content, optimize the fermentation process, and increase the functional value of fermented dairy products, which can support body health, maintain the immune system, and potentially reduce cancer. Additionally, alfalfa has been shown to extend the shelf life of products due to its antimicrobial and antioxidant properties, which inhibit the growth of pathogenic microorganisms. Challenges such as antinutritional content and the impact of alfalfa on the organoleptic and sensory characteristics of fermented dairy products can be addressed through appropriate processing methods with optimal dosing, resulting in products that not only meet basic nutritional needs but also provide positive health effects and are acceptable to consumers. Functional food innovations resulting from alfalfa fortification have great opportunities for developing fermented dairy products with higher functional values to meet consumers' demand for a variety of health-beneficial foods.